The Effect of Non Performing Loan (NPL), Independent Commissioner (KMI), and Capital Adequacy Ratio (CAR) on Firm Value (PBV) Mediated by Return on Asset (ROA) - M. Ikhsan; Sapto Jumono; Agus Munandar; Abdurrahman Abdurrahman (PT Mattawang Mediatama Solution, 2022)
The purpose of this study was to analyze the effect of Non Performing Loan (NPL), Independent Commissioner (KMI) and Capital Adequacy Ratio (CAR) on Firm Value (PBV) mediated by Return on Assets (ROA). The population of this study are all banking companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sample in this study were 22 banking companies that were selected based on the purposive random sampling method. This study was conducted with a path analysis approach using panel data regression analysis on Eviews 10. The results of this study conclude the following: NPL has a negative and significant effect on ROA, KMI has a positive and significant effect on ROA, CAR has a positive and insignificant effect on ROA, NPL has a positive and insignificant effect to PBV, KMI has a positive and significant effect on PBV, CAR has a significant and positive effect on PBV and ROA has a significant positive effect on PBV. The relationship between NPL and PBV mediated by ROA shows that it is fully mediated. Meanwhile, the relationship between KMI and CAR on PBV mediated by ROA shows that there is a partial mediated.